Factors Influencing Antenatal Care (ANC) Visits for Pregnant Women at the Rembang Community Health Center, Purbalingga Regency, Central Java - Ndari Melinda; Ayu Fitriani; Sri Sahayati; Merita Eka Rahmuniyati (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Antenatal care is health care provided by health workers for pregnant women and their fetuses. Antenatal care that is dobe regularly with a minimum of four times during pregnancy can detect early abnormalities and risk that may arise during pregancy. However, the achiecement of antenatal care coverrage in Purbalingga Regency is still not in accordance with the specified target. The K4 target set was 98% while the achicevement was 94%. This research conducted to determine the factors that influence antenatal care visits among pregnant women at the Rembang Health Center, Purbalingga Regency, Centar Java. The research method used was quatitative with a cross sectional approach. The pupulation in this study were all pregnant women who checked their pregnancy at the Rembang Health Center as total 50 (total sampling). Frequency distribution is used in univariate analysis, and the chi square test is used in bivariate analysis. The statistical test revealed that the age factor (p=0,660) was not related to antenatal care visits. Prenatal care visits are linked to education (p=0,001), occupation (p=0,000), knowledge (p=0,000), and attitude (p=0,001). Knowledge, occupation, attitude, and education related to prenatal care visits.